2009
DOI: 10.1002/mrm.21931
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution longitudinal assessment of flow and permeability in mouse glioma vasculature: Sequential small molecule and SPIO dynamic contrast agent MRI

Abstract: The poor prognosis associated with malignant glioma is largely attributable to its invasiveness and robust angiogenesis. Angiogenesis involves host-tumor interaction and requires in vivo evaluation. Despite their versatility, few studies have employed mouse glioma models with perfusion MRI approaches, and generally lack longitudinal study design. Employing a micro-MRI system (8.5T), a novel dual bolus-tracking perfusion MRI strategy was implemented. Using the small molecule contrast agent Magnevist, dynamic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 37 publications
(50 reference statements)
4
61
0
Order By: Relevance
“…T 2 maps were generated as previously described (Ardelt et al, 2012). A dual bolus DCE/DSC perfusion MRI approach was employed as previously described (Pike et al, 2009), employing a single imaging slice centered within the lesion. The DCE protocol employed a fully relaxed Paravision FLASH sequence followed by 400 rapidly acquired FLASH T 1 images as previously described (Ardelt et al, 2012), employing a femoral vein injection of Magnevist (3x diluted, 2.0 μL/g, 0.33 mmol/kg; Berlex Inc., Montville, NJ) during the series.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…T 2 maps were generated as previously described (Ardelt et al, 2012). A dual bolus DCE/DSC perfusion MRI approach was employed as previously described (Pike et al, 2009), employing a single imaging slice centered within the lesion. The DCE protocol employed a fully relaxed Paravision FLASH sequence followed by 400 rapidly acquired FLASH T 1 images as previously described (Ardelt et al, 2012), employing a femoral vein injection of Magnevist (3x diluted, 2.0 μL/g, 0.33 mmol/kg; Berlex Inc., Montville, NJ) during the series.…”
Section: Methodsmentioning
confidence: 99%
“…The calculation of ratios to contralateral hemisphere employed ROIs that were mirror images of those in the ipsilateral hemisphere, and placed in the contralateral hemisphere. Processing of perfusion MRI data was performed as previously described using the JIM software package (Pike et al, 2009; Tofts et al, 1999). Specifically, calculation of DCE-MRI parameters followed the modified model that includes a blood plasma volume term (vp) (Tofts et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…MRI is routinely employed to estimate tumor volume using anatomic images, but also tumor-associated edema and tumor cellularity using the apparent diffusion coefficient (ADC) of water (10)(11)(12). Moreover, numerous microvascular parameters that appear to be well suited to the assessment of the effect of anti-angiogenic drugs can be estimated using MRI, such as blood volume, blood flow, microvessel diameter and vessel wall permeability (13)(14)(15). A recent example has shown that the extent of vascular normalization, measured by MRI, is predictive of the outcome of anti-vascular endothelial growth factor therapy in glioblastomas (16).…”
Section: Introductionmentioning
confidence: 99%
“…The parameter T c can be estimated using DSC-MRI with a non-diffusible tracer [44]. Radioactive tracers can be used to measure v e [45].…”
Section: Discussionmentioning
confidence: 99%